2009
DOI: 10.1128/iai.00698-09
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Study of Pseudomonas aeruginosa Outer Membrane Protein Immunogenicity Using Self-Assembling Protein Microarrays

Abstract: Pseudomonas aeruginosa is responsible for potentially life-threatening infections in individuals with compromised defense mechanisms and those with cystic fibrosis. P. aeruginosa infection is notable for the appearance of a humoral response to some known antigens, such as flagellin C, elastase, alkaline protease, and others. Although a number of immunogenic proteins are known, no effective vaccine has been approved yet. Here, we report a comprehensive study of all 262 outer membrane and exported P. aeruginosa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 44 publications
1
72
0
Order By: Relevance
“…Increased fitness was not specific for Tn insertions into genes encoding for all outer membrane proteins (OMPs) although, as among the Tn insertions in the 262 genes predicted to encode for OMPs (17,18), only 68 were able to colonize the cecum (Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Increased fitness was not specific for Tn insertions into genes encoding for all outer membrane proteins (OMPs) although, as among the Tn insertions in the 262 genes predicted to encode for OMPs (17,18), only 68 were able to colonize the cecum (Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we screened a P. aeruginosa protein library (15) and identified OprL, PopB, and FpvA as Th17-stimulating protein antigens. We further evaluated PopB, as it is a highly conserved, known virulence factor, and found that PopB possesses strong Th epitope(s) as well as one or more nonprotective B-cell epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PopB has been reported to elicit a humoral immune response in patients with cystic fibrosis (CF) with P. aeruginosa lung infection (15,31), indicating its immunogenicity during infection. We did not assess the vaccine potential of FpvA due to the recently described high genetic variation of the fpvA gene, resulting in extensive sequence polymorphism of this protein when expressed by different P. aeruginosa strains (32,33).…”
Section: Protective Efficacy Of Popb Vaccinationmentioning
confidence: 99%
See 2 more Smart Citations